METHOD OF IMPERATIVE VARIABLES FOR SEARCH AUTOMATION OF TEXTUAL CONTENT IN UNSTRUCTURED DOCUMENTS - Boiko, V. O. (Radio Electronics, Computer Science, Control, 2024)
Context. Currently, there are a lot of approaches that are used for textual search. Nowadays, methods such as pattern-matching and optical character recognition are highly used for retrieving preferred information from documents with proven effectiveness. However, they work with a common or predictive document structure, while unstructured documents are neglected. The problem – is automating the textual search in documents with unstructured content. The object of the study was to develop a method and implement it into an efficient model for searching the content in unstructured textual information. Objective. The goal of the work is the implementation of a rule-based textual search method and a model for seeking and retrieving information from documents with unstructured text content. Method. To achieve the purpose of the research, the method of rule-based textual search in heterogenous content was developed and applied in the appropriately designed model. It is based on natural language processing that has been improved in recent years along with a new generative artificial intelligence becoming more available. Results. The method has been implemented in a designed model that represents a pattern or a framework of unstructured textual search for software engineers. The application programming interface has been implemented. Conclusions. The conducted experiments have confirmed the proposed software’s operability and allow recommendations for use in practice for solving the problems of textual search in unstructured documents. The prospects for further research may include the improvement of the performance using multithreading or parallelization for large textual documents along with the optimization approaches to minimize the impact of OpenAI application programming interface content processing limitations. Furthermore, additional investigation might incorporate extending the area of imperative variables usage in programming and software development.